Prevalence and Associated Risk Factors of Hypertension in a Rural Community of Western Nepal: A Cross Sectional Study - Kafle, RC; Sharma, D; Paudel, N; Sapkota, S; Alurkar, VM (Journal of Advances in Internal Medicine, 2018)
Background and aim: Hypertension is a major risk factor for cardiovascular disease. Hypertension evolved as a major public problem in urban populations of many countries including Nepal, but little is known about its prevalence and risk factors in rural areas. The objective of our study was to assess the prevalence of and risk factors associated with hypertension. Methods: A community-based cross-sectional survey was carried out in November 2017 in a four days health camp where peoples from ward number eight of Suklagandaki municipality of Tanahu district were called for screening of diabetes mellitus. No prior notice was given to the population about screening of hypertension. We screened total of 568 participants. Demographics, anthropometry and two independent blood pressure (BP) readings were taken. The data was analyzed using descriptive and inferential statistics using SPSS version 18.0. Results: A total of 568 individuals were interviewed and taken complete BP, weight and height measurements. More than 1/3rd (36.26%) of the respondents were in age group 18- 39 years with mean age 47.49 ± 16.61. Nearly, 60% of the respondents were female. Whilst 17.3% were smokers and 20% reported drinking alcohol. Overall prevalence of hypertension was 41.55% and this was significantly associated with age, gender, education, size of family, smoking habits, intake of alcohol, presence of diabetes mellitus. Conclusion: The prevalence of hypertension was found to be high and it has become a important public health issue even in rural part of Nepal. Community screening program, timely detection, lifestyle modification, treatment and prevention are all important to deal